Arts and academia : the role of the arts in civic universities - Boehm, Carola (Emerald Publishing Limited, 2022)
Art schools in our universities play a big role in many ways and not only within the institutions they are situated in. When considering that the act of engaging in arts and culture has a demonstrable but indirect effect on innovation, welfare, social cohesion, entrepreneurship, local identity and the knowledge economy, our universities can and do use arts to make themselves more permeable and to provide co-created spaces of learning. This book is a timely exploration of where creative practices and arts live in our higher education communities? How do creatives shape this creative education ecosystem? How does art provide an interface between what is within and outside of our knowledge institutions? And why should all of this matter for our communities, for the economy and for our society, specifically in a post pandemic recovery. Carola Boehm explores the delightful ways that art finds itself in every corner of academia, exploring questions of where art lives in the university sector and how it interacts with the outside, interfacing with the communities beyond its boundaries, and how it got where it is today. And with all that comes the advocacy of providing a strong justification that we need creative provisions in our universities, as there are few more powerful tools left to our disposal that can glue together and heal our divided society and our fragmented humanity.
Keywords: Arts in education.; Education, Higher.; Education, Arts in Education.; Higher & further education, tertiary education.; elektronické knihy; electronic books